Drying Technologies in Food Processing - Małgorzata Nowacka; Magdalena Dadan; Urszula Tylewicz (Applied Sciences, 2023)
Recently, consumers are paying more attention to healthy diets and often seek products with a high number of bioactive compounds, such as fruit and vegetables [...]